2014
DOI: 10.1177/1557988314545380
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Needs of Urban, African American Fathers

Abstract: Fathers play a critical role in children's development; similarly, fatherhood positively affects men's health. Among the larger population of fathers relatively little is known about the parenting knowledge of urban, African American fathers. Focusing on urban, African American fathers, the objectives of this study were to (1) understand the primary sources from which fathers learn about parenting, (2) determine where and how fathers prefer to receive future parenting education, and (3) explore the information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…90 Black fathers involved in raising their preschool-aged children note unique concerns about keeping their children safe in violent neighborhoods and seek strategies for monitoring and educating children about safety and ways to improve community life. 91 Pediatric health care providers should be aware that, although black fathers are indeed eager to learn about child rearing, researchers report they prefer to receive information from relatives or community-based organizations rather than from health care providers, 92 so making connections within the community may be the best way to reach fathers and families. More data are now available on the diversity of Hispanic fathers and the importance of understanding cultural differences, but there are still large research gaps in our understanding of at-risk children of non-English-speaking fathers or displaced undocumented immigrant fathers and of cultural differences more broadly.…”
Section: Improved Understanding Of Other Groups Of Fathersmentioning
confidence: 99%
“…90 Black fathers involved in raising their preschool-aged children note unique concerns about keeping their children safe in violent neighborhoods and seek strategies for monitoring and educating children about safety and ways to improve community life. 91 Pediatric health care providers should be aware that, although black fathers are indeed eager to learn about child rearing, researchers report they prefer to receive information from relatives or community-based organizations rather than from health care providers, 92 so making connections within the community may be the best way to reach fathers and families. More data are now available on the diversity of Hispanic fathers and the importance of understanding cultural differences, but there are still large research gaps in our understanding of at-risk children of non-English-speaking fathers or displaced undocumented immigrant fathers and of cultural differences more broadly.…”
Section: Improved Understanding Of Other Groups Of Fathersmentioning
confidence: 99%
“…Compared with women, men searched for information about pain and childbirth, health care, caring for women after childbirth, and emotional/relational issues to a greater extent. The 21 urban, African American fathers participating in the focus groups conducted by T. K. Smith et al (2015) reported appreciating information after the birth of a child about child rearing, developmental milestones, communicating effectively with children, and health information.…”
Section: Information Needsmentioning
confidence: 99%
“…The fathers in T. K. Smith et al's (2015) study learned about parenting primarily from interpersonal sources such as relatives, community members, home, and members of a church community. Participants also obtained information from books, brochures, and other written documents.…”
Section: Information-seeking and Intervening Variablesmentioning
confidence: 99%
See 2 more Smart Citations